A STUDY ON THE EFFICACY OF NEGATIVE PRESSURE APPLICATION IN THE MANAGEMENT OF PRESSURE ULCERS - Singh, A K; Ray, A; Kumar, V (Indian Journal of Plastic Surgery, 2000)
In 22 patients with pressure ulcers negative pressure was applied using adhesive drape and suction drain. By this method open wounds were converted into a controlled closed wound. It was found to reduce the tissue oedema, induration, bacterial content of the wounds, wound size, and discharge. Negative pressure was found to favour granulation tissue formation. This technique is cost effective and can be an adjuvant management of chronic infected wounds.
Keywords: Pressure; Negative; Ulcer